Potensi Kontribusi Institusi Pendidikan Islam Terhadap Perkembangan Bank Syariah di Indonesia - Asnaini, Asnaini; Oktarina, Amimah (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
Market share of Islamic banking in Indonesia is considered still small when compared to other majority Muslim countries. Currently the Indonesian sharia banking market share is only around 5.7 percent. But so far, the form of support from the Government to strengthen the role of Islamic education institutions in the utilization of Islamic banking in Indonesia is still very minimal. Therefore, this paper will reveal the potential of Islamic education institutions in developing Islamic banking in Indonesia. With the library method, an in-depth study of the topics discussed is conducted. The results of his discussion that the number of PTKIN in Indonesia as many as 58 PTKIN spread throughout Indonesia both UIN, IAIN, and STAIN. To increase the rate of development of Islamic banking, namely the Political Will Government to provide great support in the field of cooperation in Islamic Education Institutions with Islamic banking as a service used for payment traffic and community Break Up Trust towards Islamic banking by directing students especially to become sharia banking customers.